Acquisition of protease resistance by prion proteins in scrapie-infected cells does not require asparagine-linked glycosylation. - Taraboulos, A (1990)
The scrapie and cellular isoforms of the prion protein (PrPSc and PrPC) differ strikingly in a number of their biochemical and metabolic properties. The structural features underlying these differences are unknown, but they are thought to result from a posttranslational process. Both PrP isoforms contain complex type oligosaccharides, raising the possibility that differences in the asparagine-linked glycosylation account for the properties that distinguish PrPC and PrPSc. ScN2a and ScHaB cells in culture produce several PrP molecules with relative molecular masses of 26-35 kDa and proteinase K-resistant cores of 19-29 kDa. When the cells were treated with tunicamycin, this heterogeneity was eliminated and a single PrP species of 26 kDa was observed. Several hours after its synthesis, a fraction of this protein became insoluble in detergents and acquired a proteinase K-resistant core, thus displaying two of the biochemical hallmarks of PrPSc. Synthesis in the presence of tunicamycin restricted the proteinase K-resistant cores of PrP to a single species of 19 kDa. No proteinase K-resistant PrP was found in uninfected cells. Expression of a mutated PrP gene lacking both asparagine-linked glycosylation sites in ScN2a cells resulted in the synthesis of 19-kDa proteinase K-resistant PrP molecules. We conclude that asparagine-linked glycosylation is not essential for the synthesis of proteinase K-resistant PrP and that structural differences unrelated to asparagine-linked oligosaccharides must exist between PrPC and PrPSc. Whether unglycosylated PrPSc molecules are associated with scrapie prion infectivity remains to be established.